Disrupting U.S. Critical infrastructures: When and why China or Russia confess? - The probability of State-sponsored Russian; Chinese cyber breaches of U.S. critical infrastructures is nearly 100 percent. The obvious question for the United States; government security professionals then becomes not whether to act; but how to get China; Russia to confess to the crime. Under what circumstances will Russia; China remain silent if the prisoner's dilemma suggests that their dominant strategy after an attack is to defect (confess)? Why are these nations not conceding or considering owning up to any attacks on U.S. critical infrastructures? The paper uses the prisoner's dilemma to characterize; explore when; why Russia; China will confess in a simulated scenario of cooperation against the United States in cyberspace. Specifically; a coordinated attack against the U.S. energy infrastructures; including power generating plants; transmission lines; et al. (Communications of International Proceedings, 2021)
The probability of State-sponsored Russian and Chinese cyber breaches of U.S. critical infrastructures is nearly 100 percent. The obvious question for the United States and government security professionals then becomes not whether to act, but how to get China and Russia to confess to the crime. Under what circumstances will Russia and China remain silent if the prisoner's dilemma suggests that their dominant strategy after an attack is to defect (confess)? Why are these nations not conceding or considering owning up to any attacks on U.S. critical infrastructures? The paper uses the prisoner's dilemma to characterize and explore when and why Russia and China will confess in a simulated scenario of cooperation against the United States in cyberspace. Specifically, a coordinated attack against the U.S. energy infrastructures, including power generating plants, transmission lines, and distribution transformers.